Toward a New Civic Leadership: The Africana Criminal Justice Project - Ward, Geoff K. (Social justice, 2003)
Part of a special issue on war, dissent, and justice from the perspective of scholars, activists, and former U.S. political prisoners. An overview is provided of the Africana Criminal Justice Project, an education, research, and organizing initiative that is working to help in the identification and elimination of aspects of racialized social and political exclusion that are developed, reproduced, and strengthened by past and present U.S. criminal justice policy. It is noted that the project is undertaking this work as part of an effort to reframe policy and academic debates on issues of criminal and race justice and to mobilize initiatives that will address the critical situation of racialized mass incarceration. Key to the movement, it is explained, is the organization of civic leadership among former prisoners and within communities confronting the staggering collateral outcomes of the overdevelopment of the prison.